Spit It Out West Virginia: a perspective of smokeless tobacco cessation and education in rural West Virginia - Donald Reed; Stephanie Lusk; Truman Dangerfield; Mallory Ball; Janna Stoner; Michele Bowles (Frontiers in Public Health)
This article highlights strategies for implementing successful rural public health campaigns by sharing insights from the Spit It Out – West Virginia Project. Active since 2007, the project expanded to Mingo County in 2023 to address high smokeless tobacco use through culturally relevant education and cessation workshops. Key components included leveraging local partnerships, tailoring campaigns to community norms, and integrating accessible support services like the West Virginia Tobacco Quitline. Outcomes demonstrated increased awareness, behavioral change, and community engagement. Our perspective offers practical lessons for designing effective, community-based interventions in rural settings to address pressing public health challenges.